1987
DOI: 10.1007/bf01658112
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric and prepyloric ulcers

Abstract: In a prospective multicenter trial, 560 patients with peptic ulcer were treated with proximal gastric vagotomy (PGV) without drainage. Four hundred ninety-three patients had duodenal ulcer (DU), 35 pyloric (PU), and 32 prepylorlc ulceration (PPU). Actuarial 5-year recurrence rates were 14%, 35 %, and 33%, respectively, and were significantly higher in PU and PPU than in DU. In a separate study, thickness of the pyloric and antrai wail was assessed in the resection specimens of patients with similarly defined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Repetitive healing and recurrence of the underlying duodenal ulcer disease led to scar-related pyloric stenosis and impaired gastric emptying [3][4][5][6]. As a result, a gastric ulcer might have developed due to hypergastrinemia and stimulated adrenergic acid secretion [7].…”
Section: Discussionmentioning
confidence: 98%
“…Repetitive healing and recurrence of the underlying duodenal ulcer disease led to scar-related pyloric stenosis and impaired gastric emptying [3][4][5][6]. As a result, a gastric ulcer might have developed due to hypergastrinemia and stimulated adrenergic acid secretion [7].…”
Section: Discussionmentioning
confidence: 98%
“…In their study on prepyloric ulcers, Muller et al [29] reported a recurrence rate of 34% after vagotomy alone compared to 11 % when the PGV was combined with a pyloroplasty. Andersen et al: [2] investigated the efficacy of PGV with and without drainage: the cumulative 5-year recurrence rate of prepyloric ulcers was 33% with PGV alone and 9% with PGV and drainage.…”
Section: Results From Our Hospitalmentioning
confidence: 99%
“…In a study of the pathogenesis of this type of ulcer, Lawson [23] advanced the hypothesis that local factors such as chronic atrophic gastritis and a disturbed functioning of the antrum are important determinants, and that acid causes the lesions in the prepyloric antrum altered by inflammation. Histological examinations and morphometric measurements by Muller et al [29] re vealed a significantly thicker wall of pylorus and antrum in patients with prepyloric ulcers than in those whose ulcers where in located intra-or postpyloric sites. Fur thermore they found an increased degeneration of gan glionic cells which indicates dystrophic neuromuscular alterations.…”
Section: Results From Our Hospitalmentioning
confidence: 99%